University Governance and Organizational Commitment to Build Competitive Advantage in Islamic Higher Education - Akbar, Rofiq Faudy; Ahmad, Nur (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to investigate 1) Implementing university governance at State Islamic Religious College (hereinafter abbreviated as PTKIN) on the north coast (Pantura) of Central Java, 2) Differences in organizational commitment, 3) The effect of establishing university governance on organizational commitment, and 4) Higher education's competitive advantage seen from implementing university governance and organizational commitment. This study employed a quantitative approach with a questionnaire as a data collection tool. The research results demonstrated that, first, the principles of university governance at PTKIN in Central Java, especially in Kudus, Semarang, and Pekalongan, have been effectively implemented. Second, the analysis test revealed no noteworthy difference in the organizational commitment among the PTKIN managers. Third, the university governance variable (X) influenced organizational commitment (Y). In other words, the better the university governance implementation, the higher the structural officials' organizational commitment. Fourth, for an organization to thrive and achieve exceptional performance, it must possess advantages beyond mere cost-based and product-based advantages. Despite some deficiencies, the implementation of university governance and organizational commitment exposed effectiveness and efficiency. As such, State Islamic Universities in these areas have the potential to develop and progress.